Inauthenticity at Work: Moral Conflicts in Marketoriented Welfare Organizations - Thunman, Elin (Nordic Journal of Working Life Studies, 2013)
The number of employees who develop work-related problems due to stress and other mental tensions has increased in Europe during the last decades, especially among women. One explanation of the female dominance is that women more often than men work in the service and health care sector. Consequently, they are more involved in human relations at work, involving more “emotion work” or “interaction work”. Emotion researchers have described low well-being and mental disorders related to work stress in terms of inauthenticity, as suppressing one’s true emotions. In this article, a social constructivist and contextual perspective on the self is adopted. Based on case studies at Swedish work settings, the article explores the connection between authenticity and values attached to the self and the impact of the organizational setting for their realization in interaction work. Work-related stress is examined in the light of the implementation of new public management rationales and directives in welfare organizations, with particular focus on customer-orientated management. The main conclusion is that, regardless of gender, stress and mental problems could be seen as effects of feelings of inauthenticity, caused by experiences of being prevented from realizing interpersonal self-values in personal encounters at work. Women more often work in the welfare sector and are consequently more often subjected to these moral dilemmas, enhanced by customer orientation. These premises form the background for the article’s understanding of women’s more frequent development of mental stress symptoms. The article contributes to the understanding of women’s stress-related problems at work as a phenomenon in the intersection point between the individual and the organization and to the revealing of the interpersonal consequences of the increased customer orientation in the welfare area. Furthermore, by examining the contextual and situational dimensions of authenticity at work, the article adds to the knowledge about being authentic in today’s world.